Quality experience evaluation kit for online learning / Mohd Norafizal Abd Aziz … [et al.] - Abd Aziz, Mohd Norafizal; Noradzan, Haslinda; Zakariah, Zazaleena; Ismail, Juhaida; Abdul Rahman, Rozeleenda (Universiti Teknologi MARA, Pahang, 2022)
The pandemic has recently impacted the teaching and learning perspectives with the implementation of online learning. Currently, various operating procedures reflect the online learning implementation, which the autonomy provided to the practitioners. However, the implication of the quality of experiences for the online learning implementation shall support the procedures available to enhance and improve the systems to understand the proper execution of online learning. Therefore, we conducted a Quality of Experiences Kit, also known as QeeKIT, as a mechanism to evaluate the online learning experience from the learners’ perspective. The instruments include the survey regarding the learners’ experiences on the online learning implementation. The tools include the learners’ outcome, assessments, delivery, network coverage, network delay and error, devices capabilities, locations, and online resources that collected the learners’ experiences to at least discover the implication of the online learning implementation using the proposed kit. We had implemented it for the current and previous computer science students, taking various Computer Science courses in UiTM Pahang. This alternative will adhere to the online learning implementation and for future improvement required for higher learning institutions and practitioners to ponder the endemic and post-covid situation.